A multicenter prospective clinical study on continuous blood purification in treating childhood severe sepsis - Li, Leilei (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: To evaluate efficacy of continuous blood purification (CBP) in childhood severe sepsis through the analysis of organ function, inflammatory mediators and prognosis